PENGARUH KEBIJAKAN DIVIDEN DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI (PERIODE 2011-2013) - Roy, Jarry; Wulandari, Putu Prima (Jurnal Ilmiah Mahasiswa FEB, 2016)
The objectives of this research is to give the empirical proof about the influence of dividend policy and ownership structure to the firm value. This research uses three variable independend namely dividend payout ratio, managerial ownership and institutional ownership. The dependend variable of this research is firm value which is measured with TobinsQ ratio. This is a kind of hypotesis testing research. This research uses the period of 2011-2013. The research samples are elected by using purposive sampling method with 19 manufacture public companies as the samples. The multiple linier regression method is used to testing the hypothesis partially. The hypotesis testing results show that the dividend policy and managerial ownership influence the firm value significantly. Besides, this research also give the proofs that institutional ownership doesn’t influence the firm value. The value of determination coefficient is 0,302 shows that the independent variable change variationcan be explained by the dependends variable in this regression model is 30,2% and for another left has been explained by the other variable out of this research. Keywords : dividend policy, managerial ownership, institutional ownership, firm value, TobinsQ ratio.